Penerapan Metode Team Games Tournament Guna Meningkatkan Minat Belajar Siswa Kelas 5 SD 067090 Jl. Halat Kota Medan - Tasya Novriyanti; Fajar Utama Ritonga; Hairani Siregar; Kristina Sipahutar (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
After the passing of the Covid-19 Pandemic, it gave new impacts and challenges in the world of teaching and learning, especially for grade 5 students at SD 067090 Halat who experienced a decrease in their interest in learning. The main factor for this to happen is distance learning which makes students spend more time with smartphones. The impact after the pandemic was over, students became lazy to study at school. This decrease in learning interest affects the final grades of students later. This cannot be allowed to continue because it will not only affect the final grades of students but will also affect the development of students' traits, attitudes and ethics. The problem that exists in grade 5 students at SD Negeri 067090 is the decline in student interest in learning. The monotonous class atmosphere with only material explanations and doing assignments is one of the reasons students feel bored studying in class. Team Games Tournament is a learning procedure that provides opportunities for groups to compete with other groups so that students are passionate about learning. The system applied in this method emphasizes games (games) as learning activities that aim to spur the motivation and spirit of competition in students both physically and mentally with predetermined rules so as to make students enthusiastic during the learning process.